2018
DOI: 10.1200/jco.2018.36.18_suppl.lba3503
|View full text |Cite
|
Sign up to set email alerts
|

A UNICANCER phase III trial of hyperthermic intra-peritoneal chemotherapy (HIPEC) for colorectal peritoneal carcinomatosis (PC): PRODIGE 7.

Abstract: LBA3503 Background: Promising results have been obtained during the last decade using cytoreductive surgery (CRS) plus HIPEC for selected patients with colorectal PC who are amenable to complete macroscopic resection. This is the first trial to evaluate the specific role of HIPEC, after CRS, for the treatment of PC of colorectal origin. Methods: Prodige 7 is a randomized phase III, multicenter trial. Patients with histologically proven and isolated PC, peritoneal cancer index (PCI) ≤25 were eligible. Randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
193
2
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 288 publications
(219 citation statements)
references
References 0 publications
14
193
2
10
Order By: Relevance
“…Moreover, hyperthermic chemotherapy at commonly attained clinical doses had only a minor effect on the viability of several organoid lines. This indicates that current HIPEC regimens are insufficient to eradicate residual microscopic disease at least in a subgroup of patients with colorectal PMs, and this is consistent with the high recurrence rates observed after CRS–HIPEC and the negative result from the Prodige 7 trial.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Moreover, hyperthermic chemotherapy at commonly attained clinical doses had only a minor effect on the viability of several organoid lines. This indicates that current HIPEC regimens are insufficient to eradicate residual microscopic disease at least in a subgroup of patients with colorectal PMs, and this is consistent with the high recurrence rates observed after CRS–HIPEC and the negative result from the Prodige 7 trial.…”
Section: Discussionsupporting
confidence: 69%
“…As a consequence, there is currently no consensus on the choice of chemotherapy, the dose administered or the duration of perfusion. Regardless of the chemotherapy drug used in HIPEC, recurrence rates after CRS–HIPEC are high and more than half of patients experience disease recurrence within 2 years. The added value of HIPEC after CRS has recently been questioned in light of results from the Prodige 7 RCT, which showed that adding oxaliplatin‐based HIPEC to CRS provided no survival benefit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PRODIGE 7 (NCT00769405) randomized patients after optimal CRS to oxaliplatin‐based HIPEC or no HIPEC. Median overall survival in the HIPEC arm was 41.7 and 41.2 months in the CRS‐only arm (results presented at the ASCO annual meeting in Chicago) . We now know that the current high quality standardized CRS procedures are paramount in determining the patients' outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades, the therapeutic strategy for colorectal peritoneal surface malignancy (PSM) has changed considerably from a palliative approach to an approach with curative intent by the introduction of cytoreductive surgery (CRS) followed by hyperthermic intraperitoneal perioperative chemotherapy (HIPEC) . This combined treatment modality has resulted in significant survival improvements with a median overall survival of 41.7 months and should now be considered standard of care for colorectal PSM (results presented at the American Society of Clinical Oncology [ASCO] annual meeting in Chicago) . Although, there is now a clearly defined standardization of CRS procedures, based on the work of Sugarbaker et al, there is still a large variety in HIPEC treatment modalities used in current clinical practice.…”
Section: Introductionmentioning
confidence: 99%